Plant Unsaturated Fatty Acids: Biosynthesis and Regulation - He, Mei; Qin, Chun-Xue; Wang, Xu; Ding, Nai-Zheng (Frontiers in Plant Science, 2020)
In most plants, the major unsaturated fatty acids (UFAs) are three C18 species, namely, oleic (18:1), linoleic (18:2) and α-linolenic (18:3) acids. These simple compounds play multiple crucial roles in planta and are also important economic traits of oil crops. The enzymatic steps of C18 UFA biosynthesis have been well established. However, the associated FA/lipid trafficking between plastid and the endoplasmic reticulum remains largely unclear, so does the regulation of the expression and activities of the involved enzymes. In this review, we will revisit the biosynthesis of C18 UFAs with an emphasis on the trafficking and present an overview of the key enzymes and their regulation. Of particular interest is the emerging regulatory network composed of transcriptional factors and upstream signaling pathways. The review thereby provides the promise of using physical, biochemical and/or genetic means to manipulate FA composition and increase oil yield in crop improvement.